Ultrasonic absorption evidence for structural fluctuations in frog virus 3 and its subparticles. - Robach, Y (1983)
The structural fluctuations specific to self-assemblies of biological molecules have been investigated further with ultrasonic techniques by using frog virus 3 (FV3). We compared the ultrasonic properties of complete FV3 virions and of several subparticles that may be obtained from this DNA virus: (i) the central nucleoprotein core versus its component DNA and proteins in a dissociated state; (ii) the core versus the capsidless subparticle, consisting of the core surrounded by the lipid membrane; and (iii) the complete virus versus the capsidless subparticle. The ultrasonic absorption by the core particle was quite large compared with the absorption by other nucleoprotein assemblies, suggesting that the core contains some organized structure. Both the core and the complete virus absorbed ultrasound more than did the capsidless subparticle. The difference spectrum for the virion relative to the capsidless subparticle may represent a single relaxation and is analyzed, by using a recent model, in terms of volume fluctuations due to radial movements in the virion. These fluctuations are much smaller than can be detected in virus crystals with present-day x-ray techniques.